Tracing the Progress of Buya Hamka in Medan, East Sumatra (1936-1945) - Suhada, Fikri; Yasmin, Nabila (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This article aims to find out the reasons for Buya Hamka (1981) living in Medan, East Sumatra, socio-political conditions in East Sumatra during his residence there, and his role in socio-political life in East Sumatra from 1936-1945. This research uses a historical method which starts from the heuristic stage, by collecting primary sources in the form of Buya Hamka's works, including Kenang-kenangan Hidup, as well as the Pedoman Masjarakat magazine which was published in 1936 and 1938, then carrying out a process of verification and interpretation of historical facts. This research found that, when Buya Hamka lived in Medan, he was not only chief editor, but also consul of Muhammadiyah in 1939 after being elected to the 28th Muhammadiyah congress. When Japan came to Indonesia in 1942, Buya Hamka became a Japanese advisor in government and Islamic affairs. He did this not because he wanted to be a Japanese loyalist, but he did it to protect Muhammadiyah East Sumatra from being disbanded by Japan.